2004
DOI: 10.1111/j.174-1617.2004.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mutual Partner‐abuse Claims in Child Custody and Access Cases

Abstract: This article explores issues associated with mutual claims of domestic violence in the context of research on gender and violence, and in the context of litigation tactics commonly employed by perpetrators in child custody and access cases. Quotations from parents involved in such cases illustrate why accurate assessment of mutual cliams requires complete information about social context and the analysis of patterns of domination, power and control in the relationship over time. Recent developments in Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…To reconcile these conflicting stories, a naïve professional in the family court system may dismiss or minimize the claims of both spouses or erroneously conclude that the abuse is mutual when it is not. Alternatively, a women's advocate may immediately harbor the suspicion that the male must be the perpetrator and lying about his allegations or denials (Neilson, 2004). There are a number of steps to avoiding premature or erroneous judgments.…”
Section: Credibility Of Allegationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reconcile these conflicting stories, a naïve professional in the family court system may dismiss or minimize the claims of both spouses or erroneously conclude that the abuse is mutual when it is not. Alternatively, a women's advocate may immediately harbor the suspicion that the male must be the perpetrator and lying about his allegations or denials (Neilson, 2004). There are a number of steps to avoiding premature or erroneous judgments.…”
Section: Credibility Of Allegationsmentioning
confidence: 99%
“…Third, whether there is a primary perpetrator of the violence (rather than it being mutually instigated or initiated by one or the other party on different occasions) will indicate whose access needs to be restricted and which parent, if either, is more likely to provide a nonviolent home, other things being equal (Nielson, 2004). Accounts of the violent incident(s) by the participants themselves should be assessed with caution, because victims may tend to assume more blame, and abusers usually minimize or deny their conduct.…”
Section: Introductionmentioning
confidence: 99%
“…The stage of a relationship is important because the rates of domestic violence may be elevated in separating/divorcing couples as opposed to continuing couples, regardless of sexual orientation. For example, Neilson (2004) found that 40 -50% of all separating and divorcing couples in Canada report abuse in the relationships they leave. Relationship stage may also be related to differences between same-gender and opposite-gender couples.…”
Section: Samples Studiedmentioning
confidence: 99%
“…It is essential to examine the intent or function of the violence in each couple. Thus in discussing the rate of domestic violence in all separating and divorcing couples in Canada, Neilson (2004) suggests that:…”
Section: Violence Versus Abusementioning
confidence: 99%
“…34 In current practice, screening protocols can include one or more of the following: the administration of a written questionnaire, 35 the conduct of a screening interview, a check of court and public records, and continued watchfulness for evidence of domination and control. 36 There was consensus that, when cases of domestic violence are identified or when initial screening is insufficient to confirm or rule out the presence of domestic violence, families should be individually considered and referred to appropriate services and court processes. As a part of the screening and review process for each family, risk and protective factors should be identified and mitigated or supported, respectively.…”
Section: Tension #2 Screening and Triage: Simplicity And Nuancementioning
confidence: 99%